MND for Helping People with Different Disabilities - Wael Hosny Fouad Aly (International Journal of Distributed Sensor Networks)
This paper introduces a monitoring and navigation system to help people with disabilities ( MND WSN ). The proposed system is based on wireless sensor networks. In the MND WSN system, each disabled person uses a handheld smart phone device. Three types of disabilities are studied in this paper: (1) blind, (2) deaf, and (3) on wheelchair. We experimented with a three-floor university building. Sensor nodes and cameras are scattered in all rooms and hallways. Smart phones are used to communicate with the sensor nodes to take instructions to navigate through the appropriate path. Dijkstra's algorithm is used for navigation. MND WSN also monitors the disabled person while navigating. The proposed system is compared to a baseline reference experiment. Results show improvement of 34% compared to the baseline reference experiment.